6 - The African diaspora in times of COVID-19: Tourism and itinerant street vendors on the southern European border - Moreno-Maestro, Susana (Africa Development, 2024)
Within a conceptual framework proposed by the African Union, which views the diaspora as a sixth African region, this article analyses the economic situation of Senegalese street vendors in the city of Seville, in the southern European border region. For this community, street trading is the most important economic activity and source of income, of which tourism is a significant market. Using an ethnographic methodology, including interviews with street vendors, City Council officials, a lawyer-activist and observation, the study examines institutional perceptions and the treatment of Senegalese street vendors within the administrative and planning processes of the public administration, and the relationship this has with tourism. The results show how ethnocentric prejudices and criminalising stereotypes influence local administration policy. The analysis also examines the impact of the Covid-19 pandemic in terms of the lack of institutional assistance for this population group, how the Senegalese population coped with the economic impact of lockdown through their own networks and support systems, and by migrating outward. The results presented in this article are part of a broader research project on urban development and sociospatial impacts of tourism in large cities in Andalusia, Spain (PAIDI-FEDER 2020: R+D+i Project).